2019
DOI: 10.1038/s41598-019-44149-8
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of endogenous microbiota on the molecular composition of cloud water: a study by Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR MS)

Abstract: A cloud water sample collected at the puy de Dôme observatory (PUY) has been incubated under dark conditions, with its endogenous microbiota at two different temperatures (5 and 15 °C), and the change in the molecular organic composition of this sample was analyzed by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). Microorganisms were metabolically active and strongly modified the dissolved organic matter since they were able to form and consume many compounds. Using Venn diagrams, fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 64 publications
(67 reference statements)
3
41
0
Order By: Relevance
“…Additionally, the rapidly changing conditions in clouds, like condensationevaporation and freeze-thaw cycles, can cause strong physiological shocks and physical damage to cells, which can eventually be lethal. The viability of airborne microorganisms is thus very variable in space and time depending on environmental conditions (Fahlgren et al, 2010;Hu et al, 2017;Lighthart and Shaffer, 1995;Monteil et al, 2014), but yet the fact that a fraction of bacterial cells are viable was shown in many experiments of microbiological cultures from ambient aerosol samples (Amato et al, 2007b;Bovallius et al, 1978;Lighthart, 1997;Newman, 1948). This was specified and quantified more recently by direct observations and measurements of biological activity imprints (Amato et al, 2007aSattler et al, 2001;Wirgot et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the rapidly changing conditions in clouds, like condensationevaporation and freeze-thaw cycles, can cause strong physiological shocks and physical damage to cells, which can eventually be lethal. The viability of airborne microorganisms is thus very variable in space and time depending on environmental conditions (Fahlgren et al, 2010;Hu et al, 2017;Lighthart and Shaffer, 1995;Monteil et al, 2014), but yet the fact that a fraction of bacterial cells are viable was shown in many experiments of microbiological cultures from ambient aerosol samples (Amato et al, 2007b;Bovallius et al, 1978;Lighthart, 1997;Newman, 1948). This was specified and quantified more recently by direct observations and measurements of biological activity imprints (Amato et al, 2007aSattler et al, 2001;Wirgot et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the importance of aqueous phase processes increases with increasing solubility (Henry's law constants). Our recent cloud FT-ICR-MS analyses of cloud water samples have shown that about 50% of ~2100 identified compounds were utilized by cloud microorganisms (Bianco et al, 2019). Thus, microbial processes in cloud water may represent efficient sinks for numerous organics and might 375 even result in products different from those of chemical reactions (Husárová et al, 2011).…”
Section: Atmospheric Implications 355mentioning
confidence: 99%
“…CC BY 4.0 License. (Bianco et al, 2019b;Vaïtilingom et al, 2011Vaïtilingom et al, , 2013. They are also able to degrade pollutants such as phenols (Lallement et al, 2018b).…”
Section: Cloudmentioning
confidence: 99%